Torrachilty Hut-Circle: A Case Study in the Sustainable Procurement of Archaeological Projects. (May 2015) - Rees, Thomas; Ritchie, Matt
<x content-type="archive" xml:space="preserve">Abstract</x> Damage accidentally wrought during forestry harvesting operations on a known monument acted as a prompt for Forestry Commission Scotland (FCS) to explore a sustainable procurement framework for small investigative archaeological projects. The framework needed to secure and report on minor intrusive works to inform site management in an efficient manner and include the delivery of any potential environmental, social, and economic opportunities arising. Small-scale archaeological survey, excavation, and analytical work can deliver significant benefits in terms of additional wider environmental, social, and economic opportunities if they are included from the outset. Such opportunities can include: continuing professional development for contractors; outreach opportunities for local communities; recognising local educational potential; transparency and feedback within the procurement process; purposefully testing new technologies and/or methodologies and ensuring the publication of results; and fully archiving the project (from original brief through project design to final publication) in the relevant Historic Environment Record. This paper examines the work undertaken at Torrachilty hut-circle in the context of promoting good site management through an enhanced understanding of the consequences of forestry operations, building on the field research procedure suggested by Carver in the context of a small-scale, site-based, investigative archaeological project.1